Anthocyanin-Enriched Riceberry Rice Extract Inhibits Cell Proliferation and Adipogenesis in 3T3-L1 Preadipocytes by Downregulating Adipogenic Transcription Factors and Their Targeting Genes - Kongthitilerd, Phutthida (Nutrients, 2020)
Riceberry rice (Oryza sativa L.) is a new pigmented variety of rice from Thailand. Despite its high anthocyanin content, its effect on adipogenesis and adipocyte function remains unexplored. We investigated whether Riceberry rice extract (RBE) impacted cell proliferation by examining viability and cell cycle, using preadipocyte 3T3-L1 cells. To test RBE’s effect on adipocyte formation, cells were cultured in adipogenic medium supplemented with extract and adipocyte number and triglyceride levels were quantified. Furthermore, Akt1 phosphorylation along with RT-qPCR and intracellular calcium imaging were performed to obtain an insight into its mechanism of action. The effect of RBE on adipocyte function was investigated using glucose uptake and lipolysis assays. Treatment of cells with RBE decreased preadipocyte number without cytotoxicity despite inducing cell cycle arrest (p < 0.05). During adipogenic differentiation, RBE supplementation reduced adipocyte number and triglyceride accumulation by downregulating transcription factors (e.g., PPARγ, C/EBPα, and C/EBPβ) and their target genes (p < 0.05). The Akt1 phosphorylation was decreased by RBE but insignificance, however, the extract failed to increase intracellular calcium signals. Finally, the treatment of adipocytes with RBE reduced glucose uptake by downregulating Glut4 mRNA expression and enhanced isoproterenol-induced lipolysis (p < 0.05). These findings suggest that RBE could potentially be used in the treatment of obesity by inhibiting adipocyte formation and proliferation.